Urgensi Guru Bimbingan dan Konseling di Sekolah Dasar - Mustikaati, Wina; Fitriyani, Devita; Laura, Putri (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The absence of guidance and counseling (BK) teachers in primary schools can have a negative impact on students' social and emotional development. Without proper guidance, students are at risk of experiencing difficulties in managing emotions, building healthy social relationships and facing academic challenges, which can ultimately hinder their overall growth. This study aims to explore the important role of guidance and counseling teachers in supporting student development in primary schools. Through a qualitative approach, data was collected from interviews with teachers, students, and parents to understand the impact of the presence of counseling guidance services. The results showed that guidance and counseling teachers not only help students in academic aspects, but also play a role in the development of social and emotional skills. With these services in place, students are better able to cope with personal and social problems, and increase their self-confidence. The findings emphasize the importance of integrating counseling guidance services in the education system to create a more supportive and inclusive learning environment.